Métodos alternativos de resolução de conflitos: desafios dos movimentos de extrajudicialização da justiça por meio das novas tecnologias - Padilha, Leonardo Lopes (2023)
The judiciary system has been challenged in its effectiveness to provide legal protection in regard to fundamental rights and constitutional principles, what conflict with the rationalist paradigm of the process, emerging a crisis situation. The emergence of the technological phenomenon, in the context of the networked society, reinforces this crisis through expansion of new tier of rights and judicial procedures in today’s society, antagonizing the legitimacy of the judge in the exercise and protection of constitutional foundations, a situation that exacerbates the difficulties in implementation of a appropriate due process considering the democratic rule of law. In response to the difficulties of conventional legal process, new technological legal designs are created, more specifically implemented by technological alternative systems or alternative extrajudicial means. This study proposes to reflect on the impacts, limits and possibilities in the legal system and the limits of new alternative methods of justice. Starting from the theoretical premise of the Brazilian jurisdiction crisis, sought to understand the application of technology in the conflict resolution system and the challenges created by the procedural technological turn to answer the question of what extent the technological means of extrajudicialization affect the realization of rights. To explore this matter, the work elaborated as research problem: to what extent does the movement of technological exrtajudicialization of justice adequately respond to overcoming the crisis of jurisdiction, promoting the exercise of rights in an accessible and democratic way? The general objective is to investigate the impact of extrajudicialization through technologies in the context of the jurisdiction crisis, exploring its restrictions and potential in the search for equitable, easily accessible and democratic justice, observing the impact of the procedural technological turn. The study has as its theoretical and legal basis the theory of the jurisdictional crisis, mainly through the developments of Ovídio Baptista da Silva. The research used the phenomenological approach method. The bibliographic method was used as a method of procedure, instrumented by documentary and bibliographic analysis techniques through records, simple and expanded summaries. Finally, it was concluded that the state of the jurisdiction crisis, based on the rationalist paradigm, can be overcome, although partially, through restructuring the procedural law to extrajudicial means, allowing technological instruments to have an architecture oriented to the integrity of fundamental rights indicated by constitutional procedural principles in order to give concreteness to rights, without the capture of the system of protection of rights by sectors of interest.